Mengkritisi Iklan Layanan Masyarakat (ILM) Kita - Udin, Noor (Bina Nusantara University, 2011)
Public service advertising is becoming one way to reach communication purpose in Indonesia from both public and private institutions. However, more public service advertisings are having problems in its internal surrounding. For instance, dishonesty factor to be presented, only lips service or to cover weakness of an organization or corporation. The critical review will aim to one balance understanding about how public service advertising presents well from who delivered the message, to what purpose the advertising is delivered and how, and to which community groups the advertising is aiming. Finally, the public service advertising will be the effective way because it has variables that supposed to be had by public service advertising.